An efficient routing protocol for mobile ad hoc networks with Neighbor Awareness and Multicasting - Pathan, Al-Sakib Khan; Alam, Md. Mahbub; Monowar, Md. Mostafa; Rabbi, Md. Forhad (IEEE USA, 2004)
An ad hoc Network is built on the fly where a number of mobile nodes work in cooperation without the engagement of any centralized access point or any fixed infrastructure. In this paper, we proposed an efficient routing protocol for ad hoc networks which we named as NAMP (Neighbor Aware Multicast Routing Protocol). NAMP aims at achieving higher performance by reducing control overhead and improvement of the endto-end delivery of data packets. It is a tree based, hybrid multicast routing protocol. For route creation, NAMP uses the neighboring information and dominant pruning approach. It uses secondary forwarder method for route maintenance.